VD_FINDINFO Plainte / 2012 / 56 vom 7. Januar 2013 - VD Tribunal cantonal (2013)
ACTION RÉVOCATOIRELP, OUVERTURE DE LA FAILLITE, OBJET SÉQUESTRÉ | 17 LP, 18 al. 1 LP, 199 al. 1 LP, 206 al. 1 LP, 285 al. 1 LP